Social support and quality of life among the elderly in Ibadan metropolis (2022)
This study examines social support and quality of life among the aged in Ibadan metropolis. It adopted a descriptive research design. A total of one hundred elderly in Ibadan metropolis were selected using simple random sampling technique. Questionnaires consisting of socio-demographic characteristics and sections which is on quality of life = .83 and social support = 89. Four research questions were tested and answered using descriptive statistics, PPMC and regression at 0.05 level of significance. Findings showed that the level! of social support is high (=3.10> 3.00) and level of quality of life is high (=1.93< 3.00) and there is a significant relationship between social support and quality of life among the elderly in Ibadan metropolis; r (98) =. 786p <0.05. Gender (β =. 107, p<0.05), age (β= .100, p<0.05) and educational qualification (β= .129, p<0.05) had a significant relative contribution to the quality of life among the elderly in Ibadan metropolis. It was recommended among others that the elderly people should be encouraged and motivated to have a better quality of life, while social workers should help in one-on-one counselling of the elderly people on the quality of life